Capital Structure and Value Creation in Listed Oil and Gas Companies in Nigeria - Aderibigbe, Amos Adejare; Babatunde, Shakirat Adepeju; Babalola, Olufisayo; Ayilara, Modinat Abiola (Sinergi International Journal of Accounting and Taxation, 2025)
Value creation (VC) increases shareholder value and maintains a competitive advantage; however, most companies tend to miss their mark in creating consistent value due to suboptimal capital structure (CS) choices. The primary objective of this study is to assess the nexus between CS and VC among listed oil and gas (O&G) companies in Nigeria. CS is represented by the debt-equity ratio (DER), the equity-to-total assets ratio (ETAR), and the total debt-to-total assets ratio (TDTA). VC is proxied by return on equity (ROE) and Tobin’s Q (TOQ). The data employed in the study were secondary data sourced from audited financial statements of the eight listed O&G firms in Nigeria between 2014 and 2023. The panel data regression analysis was guided by the Hausman test. The results of the findings showed that DER and ETAR have inverse and positive significant effects, respectively, on ROE. TDTA has an inconsequential adverse effect on ROE. DER has a significant adverse relationship with TOQ at the 10% level. ETAR and TDTA have direct and negative insignificant relationships with TOQ, respectively. The study affirmed that there exists a distinct nexus between CS and VC. Firms are encouraged to reinforce equity financing to create value.